Coordinated representations for naturalistic memory encoding and retrieval in hippocampal neural subspaces - Dasom Kwon; Jungwoo Kim; Seng Bum Michael Yoo; Won Mok Shim (Nature Communications)
Abstract Our naturalistic experiences are organized into memories through multiple processes, including novelty encoding, memory formation, and retrieval. However, the neural mechanisms coordinating these processes remain elusive. Using fMRI data acquired during movie viewing and subsequent narrative recall, we examine hippocampal neural subspaces associated with distinct memory processes and characterized their relationships. We quantify novelty in character co-occurrences and the valence of relationships and estimate event memorability. Within the hippocampus, the novelty subspaces encoding each type exhibit partial overlap, and these overlapping novelty subspaces align with the subspace involved in memorability. Notably, following event boundaries, hippocampal states within these subspaces align inversely along a shared coding axis, predicting subsequent recall performance. This novelty-memorability alignment is selectively observed during encoding but not during retrieval. Finally, the identified functional subspaces reflect the intrinsic functional organization of the hippocampus. Our findings offer insights into how the hippocampus dynamically coordinates representations underlying memory encoding and retrieval at the population level to transform ongoing experiences into enduring memories.